2004
DOI: 10.1111/j.1524-4725.2004.30225.x
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Multiple Keratoacanthoma Centrifugum Marginatum

Abstract: The exceptional case of a man with multiple keratoacanthoma centrifugum marginatum is reported. Treatment with methotrexate combined with oral prednisone was effective. This case illustrates how some variants of keratoacanthomas do not really fit into the current classification and how complex the treatment of these tumors is.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…The systemic administration of retinoids has been advocated as both prophylactic and therapeutic treatment for cutaneous neoplastic disorders, especially in the setting of multiple lesions 5,6 . Intralesional methotrexate, bleomycin, and interferon‐α, as well as local and intralesional 5‐fluorouracil, have been reported as therapeutic alternatives 7,8 . In our case, local application of imiquimod cream was given as the patient refused further oral or intralesional treatment.…”
Section: Discussionmentioning
confidence: 81%
“…The systemic administration of retinoids has been advocated as both prophylactic and therapeutic treatment for cutaneous neoplastic disorders, especially in the setting of multiple lesions 5,6 . Intralesional methotrexate, bleomycin, and interferon‐α, as well as local and intralesional 5‐fluorouracil, have been reported as therapeutic alternatives 7,8 . In our case, local application of imiquimod cream was given as the patient refused further oral or intralesional treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Our patient had a good and prompt response to acitretin. However, Mangas et al 13 and Das et al 14 reported failure of oral retinoids in their patients. Patients successfully treated with oral retinoids are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 95%
“…Failure of retinoid as in our case has been documented earlier. 11 The decision was taken in favor of surgical intervention and wide local excision was planned, considering the fact that the patient showed recurrence following previous inadequate excision. Following our intervention, the patient is showing no recurrence, highlighting that surgical intervention can be adopted as the preferred mode of therapy for KCM, keeping in mind that a wide excision is performed to prevent subsequent recurrence.…”
Section: Discussionmentioning
confidence: 99%